Simultaneous assessment of serum levels and pharmacologic effects of cannabinoids on endocannabinoids and N-acylethanolamines by liquid chromatography-tandem mass spectrometry - Couttas, Timothy; Boost, Carola; Pahlisch, Franziska; Sykorova, Eliska; Leweke, Judith E.; Köthe, Dagmar; Endepols, Heike; Rohleder, Cathrin; Leweke, F. Markus (Cannabis and cannabinoid research, 2023)
Introduction: The primary compounds of Cannabis sativa, delta-9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD), inflict a direct influence on the endocannabinoid system-a complex lipid signaling network with a central role in neurotransmission and control of inhibitory and excitatory synapses. These phytocannabinoids often interact with endogenously produced endocannabinoids (eCBs), as well as their structurally related N-acylethanolamines (NAEs), to drive neurobiological, nociceptive, and inflammatory responses. Identifying and quantifying changes in these lipid neuromodulators can be challenging owing to their low abundance in complex matrices. - Materials and Methods: This article describes a robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the extraction and quantification of the eCBs anandamide and 2-arachidonoylglycerol, along with their congener NAEs oleoylethanolamine and palmitoylethanolamine, and phytocannabinoids CBD, Δ9-THC, and 11-Nor-9-carboxy-Δ9-tetrahydrocannabinol, a major metabolite of Δ9-THC. Our method was applied to explore pharmacokinetic and pharmacodynamic effects from intraperitoneal injections of Δ9-THC and CBD on circulating levels of eCBs and NAEs in rodent serum. - Results: Detection limits ranged from low nanomolar to picomolar in concentration for eCBs (0.012-0.24 pmol/mL), NAEs (0.059 pmol/mL), and phytocannabinoids (0.24-0.73 pmol/mL). Our method displayed good linearity for calibration curves of all analytes (R2>0.99) as well as acceptable accuracy and precision, with quality controls not deviating >15% from their nominal value. Our LC-MS/MS method reliably identified changes to these endogenous lipid mediators that followed a causal relationship, which was dependent on both the type of phytocannabinoid administered and its pharmaceutical preparation. - Conclusion: We present a rapid and reliable method for the simultaneous quantification of phytocannabinoids, eCBs, and NAEs in serum using LC-MS/MS. The accuracy and sensitivity of our assay infer it can routinely monitor endogenous levels of these lipid neuromodulators in serum and their response to external stimuli, including cannabimimetic agents.